Re-imagining Africa as a Knowledge Economy: Premises and Promises of Recent Higher Education Development Initiatives. (March 2018) - Molla, Tebeje; Cuthbert, Denise
Africa is being re-imagined as a knowledge economy, and higher education (HE) systems have been propelled into the centre of national economic plans and strategies. This paper provides an analysis of four recent major initiatives directed to the revitalisation of HE in sub-Saharan Africa: the Pan African University (2010), the Africa Higher Education Centers of Excellence Project (2014), The Kigali Communiqué on Higher Education for Science, Technology and Innovation (2014), and the Dakar Declaration and Action Plan on Revitalising Higher Education for Africa's Future (2015). Guided by critical frame analysis, we examined assumptions and expectations of these regionally/globally structured HE development agendas. The findings show that, while there is a convergence of thinking on the promise for economic transformation held by invigorated HE sectors in Africa, there are uncritically adopted premises about how this transformation is to be achieved. In particular, we find that the promise held out for economic transformation through HE is at risk of failing through the inadequate contextualisation of global policy orthodoxies to African conditions, and that some of the premises about the nature and scale of the economic transformation required to make the re-imagined Africa a reality need to be reconsidered.